Complete mitochondrial genome of the amphidromous, red-tailed goby Sicyopterus lagocephalus (Pallas) (Teleostei, Gobiidae). (3rd September 2015) - Chiang, Tzen-Yuh; Chen, I-Shiung; Lin, Hung-Du; Hsiao, Sheng-Tai; Ju, Yu-Min
Abstract: In this article, the complete mitogenome of the amphidromous, red-tailed goby, Sicyopterus lagocephalus has been amplified and sequenced by long polymerase chain reaction. This mitochondrial genome consists of 16, 500 bp, with 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and a non-coding control region (CR), and its gene arrangement is identical to those of most vertebrates. The CR (841 bp) is located between tRNA Pro and tRNA Phe . The overall base composition of the heavy strand is A, 28.9%; G, 16.4%; C, 28.3%; and T, 26.4%, with a slight AT bias of 55.3%. The complete mitogenomic data may provide more informative for phylogenetic approach for gobioid phylogeny especially for Sicydiine gobies.